The Impact of Seasonal Variation on Salivary Hormone Responses During Simulated Mountain Warfare - Jesse A. Stein; Laura J. Palombo; Andrea C. Givens; Jake R. Bernards; Emily B. Kloss; Daniel W. Bennett; Brenda A. Niederberger; Karen R. Kelly (Physiologia)
Military personnel routinely complete stressful training exercises in harsh environmental conditions to prepare for intense operational demands. Purpose: This study determined the effect of environmental conditions on salivary hormone profiles in Marines during a mountain warfare training exercise (MTX). Methods: Two cohorts of Marines (age 22 ± 4, height 174 ± 7 cm, body mass 79.2 ± 11.5 kg) completed an MTX (elevation 2100 to 3500 m) in the Fall (n = 63, temperature 11 ± 2 °C) and Winter (n = 64, temperature −5 ± 4 °C). Saliva samples were provided before (PRE), during (MID), and after (POST) the MTX, and were assayed for α-amylase, cortisol, DHEA, testosterone, and osteocalcin. Results: Linear mixed models were used to determine significant interactions (time × season) and found differences in DHEA, testosterone, and osteocalcin. Testosterone and DHEA were lower at MID compared to PRE and POST during the Fall MTX. Testosterone was higher at MID compared to PRE and POST during the Winter MTX, while DHEA remained stable. Osteocalcin was higher in Fall participants compared to Winter but demonstrated a similar trend to increase at MID and decrease at POST in both groups. Cortisol was higher during the Winter MTX compared to the Fall. Conclusions: These findings highlight the differential physiological stress responses in varying seasonal conditions, suggesting the need for tailored training strategies to enhance military readiness and prevent hormonal dysregulation. Further research is needed to elucidate the mechanisms underlying these seasonal effects.